THE CASE REPORT OF A REBELLIOUS REFLEX SYMPATHETHIC DYSTROPHY SYNDROME: THE RELATIONSHIP OF RSD AND PSYCHOLOGIC FACTORS - Pınar Borman; Hatice Bodur; Çiğdem Aydemir (Archives of Rheumatology, 2002)
Reflex sympathetic distophy syndrome (RSDS) is a painful and disabling neurovascular condition. The treatment of RSDS is difficult and there is not a definite effective regimen. The review of the recent literature support that the personality traits, stressful life events and conflicts are important for the development of RSDS and psychiatric help may influence the progression and severity of the disease. Herein a case of RSDS who was resistant to standart therapies but responded to psychotherapy, is reported and the role of psychological factors in the development of RSDS was discussed.